(untitled) (Dhaka University Journal of Science, 2016)
The flow an heat transfer on the unstea y laminar mixe convection boun ary layer in a micropolar flui past a vertical we ge have been stu ie taking into account the effect of magnetic fiel . We assume that the free stream velocity an surface temperature oscillate in magnitu e but not in the irection of the oncoming flow velocity. The governing equations have been solve numerically by using the straight forwar finite ifference metho . The amplitu es of skin friction an couple stress are foun to be significantly epen ent on the Richar sons number, Ri, the magnetic parameter, M, an the vortex viscosity parameter, K. We observe that the amplitu es of skin friction an couple stress increases owing to an increase of the Richar sons number, Ri, while these become lower for the higher value of the magnetic parameter, M, an the vortex viscosity parameter, K. Also the results emonstrate that the effects of the parameters on the amplitu es of heat transfer are rather weak. Dhaka Univ. J. Sci. 64(1): 65-70, 2016 (January)